Metabolism of Amino Acids in Cancer - Wei, Zhen; Liu, Xiaoyi; Cheng, Chunming; Yu, Wei; Yi, Ping (Frontiers in Cell and Developmental Biology, 2021)
Metabolic reprogramming has been widely recognized as a hallmark of malignancy. The uptake and metabolism of amino acids are aberrantly upregulated in many cancers that display addiction to particular amino acids. Amino acids facilitate the survival and proliferation of cancer cells under genotoxic, oxidative, and nutritional stress. Thus, targeting amino acid metabolism is becoming a potential therapeutic strategy for cancer patients. In this review, we will systematically summarize the recent progress of amino acid metabolism in malignancy and discuss their interconnection with mammalian target of rapamycin complex 1 (mTORC1) signaling, epigenetic modification, tumor growth and immunity, and ferroptosis. Finally, we will highlight the potential therapeutic applications.